2006
DOI: 10.1111/j.1460-9568.2006.05225.x
|View full text |Cite
|
Sign up to set email alerts
|

Differential expression of otoferlin in brain, vestibular system, immature and mature cochlea of the rat

Abstract: Mutations of the human otoferlin gene lead to an autosomal recessive nonsyndromic form of prelingual, sensorineural deafness (deafness autosomal recessive 9, DFNB9). Several studies have demonstrated expression of otoferlin in the inner ear and brain, and suggested a role of otoferlin in Ca(2+)-triggered exocytosis. So far, otoferlin expression profiles were solely based on the detection of mRNA. Here, we analysed the expression of otoferlin protein and mRNA using immunohistochemistry, in situ hybridization an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
115
2
5

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(128 citation statements)
references
References 31 publications
6
115
2
5
Order By: Relevance
“…OTOF protein is highly expressed in both cochlear and vestibular hair cells of rat (Schug et al, 2006) and mouse (Roux et al, 2006) inner ears, yet mice with otoferlin mutations, although deaf, appear to have normal vestibular function on the basis of behavioral assessments. Results from behavioral tests, however, cannot exclude the possiblility that normal balance is achieved by compensation from visual or proprioceptive inputs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…OTOF protein is highly expressed in both cochlear and vestibular hair cells of rat (Schug et al, 2006) and mouse (Roux et al, 2006) inner ears, yet mice with otoferlin mutations, although deaf, appear to have normal vestibular function on the basis of behavioral assessments. Results from behavioral tests, however, cannot exclude the possiblility that normal balance is achieved by compensation from visual or proprioceptive inputs.…”
Section: Discussionmentioning
confidence: 99%
“…Auditory brainstem response (ABR) analysis demonstrates that mice homozygous for this missense mutation are profoundly deaf. Otoferlin is strongly expressed in vestibular as well as cochlear hair cells (Roux et al, 2006;Schug et al, 2006), yet mutant mice do not exhibit circling or head bobbing behaviors typical of vestibular dysfunction in mice. To directly assess receptor function, we measured vestibular-evoked potentials (VsEPs) (Jones et al, 2005), but found no evidence of vestibular deficits in deaf5/deaf5 mutant mice compared with controls.…”
Section: Introductionmentioning
confidence: 99%
“…The expression of otoferlin, which is known to be present in the brain and is essential for glutamate exocytosis at the auditory ribbon synapse and reported to be defective in a recessive form of human deafness, showed significant decrease in the hippocampus of mice exposed to repeated blasts [19][20][40][41][42]. In contrast, otoancorin, another hearing-related gene defective in autosomal recessive deafness and known to mediate the contact between the apical surface of sensory epithelial cells and acellular gels of the inner ear and the tectorial and otoconial membranes for proper auditory processing, showed significant increase in the hippocampus after repeated blast exposures [21,43].…”
Section: Discussionmentioning
confidence: 99%
“…Cadherin and protocadherin mutations were linked to digenic inheritance of deafness and have specific functional roles in noise-induced hearing loss [13][14][16][17]. Other groups of proteins involved in deafness are otoferlin and otoancorin, which are also reported to have major roles in auditory functions, including central auditory processing [18][19][20][21]. Another large class of molecules involved in auditory signaling is centered on the calcium regulating proteins, which are known to have broad functions in age-and noise-related hearing loss or protection [18,[22][23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…One first indication of such additional functions was the demonstration of its expression in a widened pattern, including the brain (25), the vestibular system, neurons and nerve fibers. Also, apart from its presence in cochlear inner hair cells, otoferlin was found to be present in mature outer hair cells responsible for low-frequency processing (30). Its subcellular distribution beyond regions of synaptic vesicle fusion and its association with Golgi markers suggested a more ubiquitous role.…”
Section: Otoferlin's Interactomementioning
confidence: 97%